First record of Tagetes imbricata (Asteraceae, Tageteae) in Peru - Schiavinato, Darío Javier (2024)
Tagetes imbricata, a species recently described from Argentina and Bolivia, is reported here for the first time from Peru based on herbaria collections and field observations available at biodiversity online repositories. This new record significantly expands the distribution area of this species to the north, covering a total of more than 2000 kilometers along the Andes Mountains. An illustration for T. imbricata is here provided for the first time, detailing morphological aspects. Two vernacular names, “kita-chick-chipa” and “chichijsa”, are reported for this species.